Countering Distrust in Illicit Online Networks: The Dispute Resolution Strategies of Cybercriminals. (August 2022) - Dupont, Benoît; Lusthaus, Jonathan
The core of this article is a detailed investigation of the dispute resolution system contained within Darkode, an elite cybercriminal forum. Extracting the dedicated disputes section from within the marketplace, where users can report bad behavior and register complaints, we carry out content analysis on these threads. This involves both descriptive statistics across the data set and qualitative analysis of particular posts of interest, leading to a number of new insights. First, the overall level of disputes is quite high, even though members are vetted for entry in the first instance. Second, the lower ranked members of the marketplace are the most highly represented category for both the plaintiffs and defendants. Third, vendors are accused of malfeasance far more often than buyers, and their "crimes" are most commonly either not providing the product/service or providing a poor one. Fourth, the monetary size of the disputes is surprisingly small. Finally, only 23.1% of disputes reach a clear outcome.